Spontanitas, Kekuatan Digital, dan Masa Depan Demokrasi: Peran Generasi Z di Indonesia, Nepal, dan Perancis - Nuruddin Al Akbar; Muhammad Syauqi Al Sunni; Awalul Tsara Fahrani; Naufal Husni Kamal (Jurnal Studi Pemuda, 2025)
The last ten years have seen the overall trend in the loss of democracy around the world identified as being connected to three significant assumptions: (1) the digital world is fully taken over by surveillance capitalism and dominated by political elites; (2) Generation Z (born circa 1997-2012) is apolitical; and (3) democratic backsliding seals the potential of renewal. In this article, the authors provide an alternative view. They investigate Gen Z activism in Indonesia, Nepal, and France. The purpose is to determine the role of Gen Z involvement in such countries in reopening the democratic space. The research design is a qualitative study using the critical discourse analysis (CDA). The paper is based on media coverage, global databases and records of the different protests worldwide. The findings indicate that democracy is not completely repressed; on the contrary, digital spaces despite monitoring and control, remain the avenues of resistance. The political activity of Gen Z is conducted through innovative spontaneity and popular culture and even in the conditions of democratic deficit, these political outpourings are the signs of the potential democratic rejuvenation. To sum up, the paper emphasizes that Gen Z members are not just the objects of democracy but also the participants of the process of creating a transnational democratic future.